PENGARUH MODEL PEMBELAJARAN LANGSUNG (DIRECT INSTRUCTION) DENGAN PENDEKATAN KONTEKSTUAL TERHADAP PEMAHAMAN KONSEP SISWA - Purnamasari, Nurkomaria; Habibi, Habibi; Hidayat, Samsun (Lensa : Jurnal Kependidikan Fisika, 2016)
This research aimed to know the effect of direct instruction model with  contextual approach toward students concept comprehension in class XI SMA PGRI Sape. The method of this research was quasy-experimental with research design was pretest-posttest control group design. Population of this research is taken from all students in grade XI IPA. The research sample used was a class XI IPA 3 as an experimental class and class XI IPA 1 as the control class. The sampling technique using Simple Random Sampling. The technique of data colletion used instrument test in the form of essays. Analysis of data using homogenity, normality test, hypothesis testing. Hypothesis test (t-test) students concept comprehension obtained t = 9.67 ≥ table = 2.002. It can be concluded that the direct instruction model with contextual approach significantly affect students concept comprehension.PENGARUH MODEL PEMBELAJARAN LANGSUNG (DIRECT INSTRUCTION) DENGAN PENDEKATAN KONTEKSTUAL TERHADAP PEMAHAMAN KONSEP SISWA